Analysing the Behaviour of Financial Risk Management and Its Impact on Success of Project - Thu Luong Huynh Anh (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2023)
In this financial oriented business world, the risk and risk measuring activities such as identifying the issues, analysing and modifying of ambiguity in the credit creation and investment behavioural decision making. (Kishk et. al. 2008) Basically, the risk management process comes when a stakeholder of a corporation or the fund allocator decides on the basis of analysis and attempts to evaluate the probable losses in any investment. To avoid this kind of risk or technically termed as the moral hazard problem, the investor has to take certain necessary action for gaining better profitability or minimize the risk of loss. The risk management strategies are termed as behavior of the financial risk (Moles, 2016). The present paper aims to study the various behavioral decision-making process of the manager or the investor of the corporation towards the profitability. It also aims to emphasizes the impact of this strategic behavior of the firm or corporation’s decision on the successful growth and establishment. The study is significant with respect to evaluate the cause and effect through the strategies implemented by the investors. It also attempted to reveal the project success story by implementing the risk averse practices. The project victory criteria are a measurable or quantifiable term of expected outcome of the running project which must be accepted by the stakeholder. Financial risk measurement is always being an implicit proportion of the management in the firm or industry. The present study adopts the descriptive research method and uses the secondary data sources published in the company’s websites and annual statements. The collected data have been analyzed by an appropriate statistical and econometrical tool to evolve the relationship between the behavioural aspects of risk management strategies and its influence on the project success of the firm. The risk management of credit on commercial bank is most essential for the benefit and stop suffering from the losses on the project. Prevention and controlling the risk of loans and advances is a tough and very challenging target for the business project. It is statistically evidence that there is an association between the profit and credit loss expense. On the whole, the present study explores the profitability and the success of the financial organization.